Circulating levels of liver enzymes and incidence of atrial fibrillation: the Atherosclerosis Risk in Communities cohort. Issue 19 (12th June 2014) - Alonso, Alvaro; Misialek, Jeffrey R; Amiin, Mohamed A; Hoogeveen, Ron C; Chen, Lin Y; Agarwal, Sunil K; Loehr, Laura R; Soliman, Elsayed Z; Selvin, Elizabeth
Abstract : Background: Elevated levels of circulating liver enzymes have been associated with increased risk of cardiovascular disease. Their possible association with atrial fibrillation (AF) has received little attention. Methods: We studied 9333 men and women, aged 53–75 years, free of AF, participating in the Atherosclerosis Risk in Communities Study followed-up from 1996 to 2010. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), and γ glutamyl transpeptidase (GGT) were measured in stored plasma samples. Incident AF was ascertained from hospitalisations and death certificates. Associations between liver enzymes and AF incidence were assessed using multivariable Cox proportional hazards models. Results: During a mean follow-up of 12 years, 1021 incident AF events were identified. Levels of AST, and to a lesser extent ALT, showed a U-shaped association with AF risk, with higher AF risk among individuals in the two extremes of the distribution in minimally adjusted models. The associations were weakened after adjustment for potential confounders. By contrast, GGT, modelled as log base 2, was linearly associated with AF risk after multivariable adjustment: a doubling of GGT levels was associated with a 20% increased risk of AF (95% CI 10% to 30%). Additional adjustment for inflammatory markers did not appreciably affect the results. Associations were not different in men and women, in whites and blacks, among never drinkers of alcohol, and among those without prevalent heart failure. Conclusions: In this community-based prospective study, higher levels of liver enzymes, mainly GGT, were associated with an increased risk of AF. The mechanisms underlying this association deserve further scrutiny.